Evidence of increased humoral endocrine organ-specific autoimmunity in severe and classic X-chromosome aneuploidies in comparison with 46,XY control subjects - Francesca Panimolle; Claudio Tiberti; Simona Granato; Antonella Anzuini; Carlotta Pozza; Andrea Lenzi; Antonio F. Radicioni (Taylor & Francis Group, 2018)
Objective: In literature, the importance of X-linked gene dosage as a contributing factor for autoimmune diseases is generally assumed. However, little information is available on the frequency of humoral endocrine organ-specific autoimmunity in X-chromosome aneuploidies. In our preliminary study, we investigated the endocrine organ-specific humoral autoimmunity relative to four different organ-specific autoimmune diseases in a group of adult 47,XXY KS patients and in adults 46,XY control males (type 1 diabetes, T1DM; Addison's disease, AD; Hashimoto thyroiditis, HT; autoimmune chronic atrophic gastritis, AG). The aim of the present study is to evaluate the frequency of autoantibodies (Abs) specific for T1DM, AD, HT, and AG in rarer higher grade X-chromosome aneuploidies (HGA) and in 47,XXY children. Design and methods: Samples from 192 Caucasian patients with an X-chromosome aneuploidy (176 patients (55 children, 121 adults) with 47,XXY karyotype (KS patients) and 16 HGA patients (eight children, eight adults)) recruited from Sapienza, University of Rome (2007-2017) were tested for Abs specific for T1DM (insulin-Abs, GAD-Abs, IA-2-Abs, Znt8-Abs), HT (TPO-Abs), AD (21-OH-Abs), and AG (APC-Abs). The results were compared to those found in 213 46,XY control subjects (96 children, 117 adults). Results: Altogether humoral organ-specific immunoreactivity was found in 13% of KS and HGA patients, with a significantly higher frequency than in the controls (p=.008). Almost 19% of HGA patients were positive for at least one of the organ-specific Abs investigated compared to 12.5% of KS patients. The frequency of the overall immunoreactivity was higher in KS children than in KS adults. The frequency of diabetes-specific Abs was significantly higher in the patient cohort than in controls (p=.005). Thyroid- and gastric-specific autoimmunity was also found in KS and HGA patients, while adrenal-specific immunoreactivity was rare. Conclusions: These results suggest for the first time that the risk of endocrine organ-specific humoral autoimmunity progressively increases with the severity of X-chromosome polisomy. The screening for diabetes-, thyroid-, and gastric-specific autoimmunity should be considered in clinical practice for identifying rare and classic X-chromosome aneuploid patients at risk of developing organ-specific autoimmune diseases.